Evaluating Ethanolic Extract of Propolis in Broiler Chicken Development and Immunity - Sanabria, Fernando; Parra , Luz Marina (Spei Domus, 2015)
Introduction: The poultry industry provides the cheapest animal protein for human consumption, producing meat with high nutritional value, but the presence of chemical antibiotic residues in this meat has caused it to be rejected. Currently, efforts are being made to guarantee food safety by using natural antibiotics that protect the chickens, the environment, and consumers. One such antibiotic is propolis, a material obtained from bees that has high flavonoid content, and also promotes broiler development. The aim of this study was to evaluate whether the addition of propolis to the broilers’ water increased their productivity and improved their immunological development. Materials and methods: The starting point for this study was a chemical characterization by high performance liquid chromatography with photodiode array detection (hplc/dad). The selected propolis was administered to the broilers and its impact on zootechnical parameters was measured. Its antimicrobial effect against reference strain Echerichia coli and the immune response against the vaccines given to the broilers was also evaluated. Results: There were improvements in weight gain and feed conversion, and the sensitivity of antibiotics to the E. colireference strain increased. There were higher titers for Gumboro and Newcastle diseases, but the opposite effect occurred with infectious bronchitis. Conclusions: Propolis is a cost-effective and technological alternative for reducing the use of chemical antibiotics in combating diseases in the poultry industry.